The future of European contract law : essays in honour of Ewoud Hondius to commemorate his retirement as Professor of Civil Law at the University of Utrecht /: essays in honour of Ewoud Hondius to commemorate his retirement as Professor of Civil Law at the University of Utrecht. (2007) - Unknown
No abstract available